Itaconic Acid-Based Hydrogels with Flame Retardancy and High-Temperature Resistance via Vat Photopolymerization 3D Printing - Li, Rong; Yu, Runhao; Liu, Chuan; Hao, Kangan; Huang, Anrong; Wu, Chong; Zuo, Xiaoling (Journal of Research Updates in Polymer Science, 2024)
Biomass-based hydrogels have received extensive attention due to their flame retardant properties and environmental friendliness. The dilemma that non-renewable energy resources are increasingly depleted, leads us to place high expectations on renewable natural clean energy, as well as to conduct in-depth research on the efficient utilization and green preparation processes for the clean energy. In this study, we introduce a green and sustainable method for the design and preparation of flame-retardant materials by integrating two new class of itaconic acid-based hydrogels in conjunction with the rapid vat photopolymerization (VP) 3D printing technology. The hydrogels prepared by this method exhibit exceptional flame retardancy, mechanical robustness and superior high-temperature resistance. This research provides novel strategies and essential guidance for the green synthesis and sustainable development of next-generation flame retardant materials.